(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The objective of this study was to examine the effect of using Small Group Discussion technique in teaching reading comprehension at eleventh grade students of SMA PGRI 1 Subang. The method of this study is quantitative with a pre-test and post-test pre-experimental design. The population of the research was 204 students from the total of three classes. The sample was obtained by using purposive sampling technique that resulting in one classes with 32 students. Those classes were then randomly assigned into the experimental and control class. The research was conducted by following the procedure giving pre-test and post-test. Pre-test was given to see the student’s basic capability in reading before the treatment was conducted. Post-test will measure the effectiveness of the treatment towards students’ reading achievement in a certain period. The data were collected from test items which are tested to the students before and after treatment. T-test was applied to calculate the data and to test the hypothesis. The results of this study are assumed to be able to determine the effectiveness of using the Small Group Discussion technique in teaching reading comprehension of eleventh grade students of SMA PGRI 1 Subang.